ChemInform Abstract: New Layered Fluorosulfide SrFBiS2. Issue 46 (24th October 2013) - Lei, Hechang; Wang, Kefeng; Abeykoon, Milinda; Bozin, Emil S.; Petrovic, Cedomir
Abstract The title compound is prepared by solid state reaction of Bi2S3 (obtained from the elements at 600 °C for 10 h), SrF2, and SrS (600 °C, 10 h).